Discovery of miRNA–mRNA regulatory networks in glioblastoma reveals novel insights into tumor microenvironment remodeling - Iulia A. Grigore; Athulram Rajagopal; Jonathan Tak-Sum Chow; Thomas J. Stone; Leonardo Salmena (Scientific Reports)
Abstract Adult glioblastoma (GBM) is a highly aggressive primary brain tumor, accounting for nearly half of all malignant brain tumors, with a median survival rate of only 8 months. Treatment for GBM is largely ineffective due to the highly invasive nature and complex tumor composition of this malignancy. MicroRNAs (miRNA) are short, non-coding RNAs that regulate gene expression by binding to messenger RNAs (mRNA). While specific miRNA have been associated with GBM, their precise roles in tumor development and progression remain unclear. In this study, the analysis of miRNA expression data from 743 adult GBM cases and 59 normal brain samples identified 94 downregulated miRNA and 115 upregulated miRNA. Many of these miRNA were previously linked to GBM pathology, confirming the robustness of our approach, while we also identified novel miRNA that may act as potential regulators in GBM. By integrating miRNA predictions with gene expression data, we were able to associate downregulated miRNA with tumor microenvironment factors, including extracellular matrix remodeling and signaling pathways involved in tumor initiation, while upregulated miRNA were found to be associated with essential neuronal processes. This analysis highlights the significance of miRNA in GBM and serves as a foundation for further investigation.